Cultural curiosity : thirteen stories about the search for Chinese roots - Khu, Josephine M. T., 1964- (University of California Press, 2001)
This is an anthology of autobiographical essays of the Chinese diaspora. Written by ethnic Chinese who were born or raised outside of China, these pieces, full of the details of everyday life, describe the experience of growing up as a visible minority and the subsequent journey each author made to China.